Pengaruh Pelatihan terhadap Kinerja Karyawan pada KSP Balo'ta di Tana Toraja - Tampang, Yulita; Baharuddin, H.; Sambara, Kordiana (Lembaga Yasin AlSys, 2025)
The impact of training on employee performance remains a critical area of research, particularly in financial institutions. However, limited studies have specifically analyzed this relationship within savings and loan cooperatives. This study aims to examine the effect of training on employee performance at the Balo’ta Savings and Loans Cooperative. The research involved 34 employees as samples, selected through written statements provided to respondents. The study applied quantitative analysis using correlation coefficient, determination coefficient, and T-test to assess the relationship between training and employee performance. The findings revealed that training significantly enhances employee performance, indicating that well-structured training programs contribute to increased efficiency and effectiveness in the workplace. These results highlight the importance of continuous employee development to improve organizational performance. This study reinforces the need for cooperatives to invest in systematic training programs to optimize employee potential and ensure sustainable growth.